Older and More Experienced? Comparing Mainland Chinese International Students in Canada on Social Cognitive Correlates of Leisure Time Physical Activity, Acculturation, and Mental Health by Study Year - Kimberley D. Curtin; Tanya R. Berry; Gordon J. Walker (The Ohio State University Libraries, 2019)
Background: Physical activity is a mandatory component of many university programs in China and there is evidence that Chinese students value physical activity for health (Chen & Liu, 2008); however, academics are generally prioritized as students advance in their studies (Ha, Macdonald, & Pang, 2010). Among international students in the United States, Asian students were found to have some of the lowest rates of physical activity, which could be linked with many combinations of cultural, environmental, and individual barriers (Yoh, Yang, & Gordon, 2008). Physical activity may aid in healthy transitions for Chinese international students. Aim: Chinese international students were compared by study year on physical activity, mental health, culture, and social cognitive theory variables. Method: First year (n = 92), second year (n = 52), and senior (n = 77) international students studying in Canada were compared on physical activity, self-efficacy, intention, access, stress, acculturative stress, subjective well-being, acculturation, and self-construal. The relationships between the social cognitive, mental health, culture variables, and physical activity were also compared. Results: Senior students perceived fewer places to do physical activity and more discrimination compared to first- and second-year students. Senior students experienced more academic pressure and guilt towards their family compared to second year students. First year students reported more general stress compared to second year students. Self-efficacy, intention, and exercise to reduce stress shared relationships with vigorous physical activity. Subjective well-being was related to moderate physical activity, and self-efficacy and independent self-construal were related to walking. Walking decreased by study year. Conclusions: Physical activity may be used to improve mental health for Chinese international students, but interventions may need to be adjusted or implemented depending on the academic stage of the student.